2009
DOI: 10.1111/j.1551-2916.2009.03264.x
|View full text |Cite
|
Sign up to set email alerts
|

In Situ X‐Ray Radiography and Tomography Observations of the Solidification of Aqueous Alumina Particles Suspensions. Part II: Steady State

Abstract: This paper investigates the behaviour of colloidal suspensions of alumina particles during directional solidification, by in situ high-resolution observations using X-ray radiography and tomography. This second part is focussed on the evolution of ice crystals during steady state growth (in terms of interface velocity) and on the particles redistribution taking place in this regime. In particular, it is shown that diffusion cannot determine the concentration profile and the particles redistribution in this reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 24 publications
(49 reference statements)
4
49
0
Order By: Relevance
“…The quantity of domains decreases with an increasing distance to the cooling finger as domains tend to overgrow each other. This behavior was also reported by Deville et al [27]. Beyond the occurrence of lamellar macro-pores, the β-TCP lamellae themselves are porous due to an incomplete sintering (Fig.…”
Section: Scaffold Morphologysupporting
confidence: 65%
See 1 more Smart Citation
“…The quantity of domains decreases with an increasing distance to the cooling finger as domains tend to overgrow each other. This behavior was also reported by Deville et al [27]. Beyond the occurrence of lamellar macro-pores, the β-TCP lamellae themselves are porous due to an incomplete sintering (Fig.…”
Section: Scaffold Morphologysupporting
confidence: 65%
“…Therefore, linear functions are not supposed to be the first choice for very high velocities and/or very high sample heights. Deville et al applied linear cooling rates of 5 K/min and they found a slight decrease of ice front velocity over time resulting in a slight increase of the structural sizes of the sample with height [27]. Figure 4b shows the pore widths of a β-TCP scaffold solidified with an onset ice front velocity of 20µm/s according to the cooling function T onset depictured in figure 4a.…”
Section: Control Of the Ice Front Velocitymentioning
confidence: 94%
“…Recently, in situ X-ray radiography and tomography observations by Deville et al [31,32] revealed that two types of crystals (Fig. 4) were initially present: a first population of lamellar crystals, with their main axis oriented along the cooling direction, and a second population of crystals, more or less lamellar, but oriented predominantly in the radial direction (perpendicular to the cooling direction).…”
Section: Microstructurementioning
confidence: 98%
“…The theory behind freeze casting was recently explicated by Zhang et al, 60 Deville et al, [61][62][63] and Wegst et al, 59 where constitutional supercooling drives instabilities (or undulations) in the freezing front that lead to the nucleation and growth of uniformly distributed, interconnected ice crystals. During solidification, the thermodynamic free energy of the system governs the phenomena of particle entrapment or rejection by the approaching freezing front 59 :…”
Section: Microstructural Controlmentioning
confidence: 99%